Does (digital) Activism Matter? Exploring the Evolution of Collective Action: The Case of Irianna’s Solidarity Movement in Greece - Ioannou, Maria (Department of Social and Political Sciences, University of Cyprus, 2019)
Recent years have been marked by an increase of protest actions across the world; since the beginning of the global financial crisis (critical) citizens disappointed by a widespread disregard of people’s needs and wishes by political and economic elites are engaging in different types of collective action asking for greater political accountability, social and economic equality, more democratic procedures in all realms of life. It is often argued that web 2.0 technologies and social networks can play a positive role in enhancing the organization and final outcome of collective actions. On the other hand, the pessimistic school of thought argues for slacktivism, which essentially undermines the essence of activism through likes and shares. This study attempts to provide more nuanced evidence regarding the role and use of social networks in protest activities. Premised on a rich theoretical background drawing on traditional and new social movement theory, political change theory, democracy and neoliberalism, the study attempts to situate the study of (digital) activism under a multidisciplinary approach. The empirical part of the study explores the solidarity movement in favor of Irianna which took place in Greece in 2017-2018. Drawing on qualitative and quantitative methods, the study investigates how Facebook was used and how it shaped the solidarity movement, what motivated users to engage in protest activities both online and on the streets, and how Facebook influenced the desired outcome of the solidarity movement. Findings suggest that Facebook operated as an important informational tool, as a space of resistance, as a venue for amplifying activism on the street and finally as a mechanism to widen the composition of activists on the streets (in terms of age and socio-political background). Despite Facebook’s important role in raising awareness and boosting a sense of solidarity among a wide range of people, the study suggests that a number of social and political conditions along with some special traits of the case contributed to the formation of a powerful and effective solidarity movement. Notwithstanding Facebook’s fertile role in Irianna’s case, it is concluded that the perception of “sheer injustice”, the identification of protestors with Irianna, and the need to protest against the authorities of a State which has lost its democratic essence, along with a general mobilization which included celebrities and experts, led people to the streets and influenced the final outcome in favour of Irianna.
Keywords: activism; social networks; ακτιβισμός; κοινωνικά δίκτυα